The bacterial burden on computer keyboards across selected university facilities at Liverpool John Moores University, City Campus, Byrom Street, Liverpool. - Emmanuel Oladipo Babafemi; Hannah Church (PLoS ONE)
Background Bacterial burden within universities is important to investigate due to the high footfall of both students and staff, who may bring contaminants from body fluids, food, and the environment. These bacterial contaminants may be harmful to both immunocompromised and immunocompetent individuals. A focus on online resources and communication with workplaces and universities bring an important issue of computer keyboards and mice becoming potential reservoirs for such bacteria.This study aimed to investigate the presence of bacteria on computer keyboards and mice across the Liverpool John Moores University campus by detecting the presence of bacterial growth, identifying these bacteria and the role of disinfection in lowering the bacterial counts and changing their diversity. Materials and method A total of 478 pre- and post-treatment swab samples were taken using sterile cotton swabs moistened in sterile nutrient broth (Thermo Scientific™ Oxoid™) from both the keyboards and mice of facilities across the university campus were cultured at 37°C on blood agar plates. A total period of 30 minutes elapsed between first sampling (pre-treatment) and disinfection before the second sampling (post-treatment). Identification of isolated bacterial species was done with Matrix-Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) mass spectrometry according to protocol by BioMérieux VITEK® MS prime. Results One hundred and fifty-four (64.4%) of pre-treatment and Forty-nine (20.5%) of post-treatment cultures showed microbial growth, which were identified as various species of Gram-positive cocci, Gram positive bacilli and Gram-negative cocci. Discussion Across the Liverpool John Moores campus computer keyboards and mice were found to be contaminated with many bacteria, all of which were identified as opportunistic and therefore are not likely to cause harm to healthy individuals. However, there is a greater risk of infection to immunocompromised individuals, which could lead to co-morbidities.